Understanding the Foundations of Electromagnetic Field Theory with Computer Software - (:unkn) unknown (IEEE, 2019)
An understanding of electromagnetic fields concepts and electrical phenomena requires advanced mathematical knowledge and analytical ability. Teaching these concepts with the use of a computer is a new design in teaching, and it promotes creative learning, which motivates students and improves their understanding of mathematical concepts, phenomena and laws. In this paper, some fundamental electrostatic and Magnetostatic field equations on specific examples which use Mathematica Software to promote a virtual environment to teach these subjects on the computer by encouraging electrical engineering students is studied.
Keywords: electrostatic field; magnetostatic field; Mathematica software; visualization; Electrical Engineering Education; TEACHING ELECTROMAGNETICS; COURSES